LncRNA PART1/miR-185-5p/RUNX3 feedback loop modulates osteogenic differentiation of bone marrow mesenchymal stem cells - Junjie Zhang; Nanwei Xu; Changlin Yu; Kaisong Miao; Qiugen Wang (Taylor & Francis Group, 2021)
Background Osteogenic differentiation of human bone marrow-derived mesenchymal stem cells (hBMSCs) is essential for bone formation, and its dysfunction is reported to be associated with osteoporosis (OP). Recent researches have determined that lncRNA PART1 participates in the pathogenesis of multiple diseases. However, its role in modulating osteogenic differentiation of hBMSCs is unclear. Methods PART1, miR-185-5p, and RUNX3 levels were assessed via RT-qPCR. The protein levels of OCN, OSN, and COL1A1 were measured by western blotting. The osteoblastic phenotype was evaluated via ALP activity and ARS staining. The relationship between miR-185-5p and PART1 or RUNX3 was validated by luciferase reporter, RIP assays. Results PART1 and RUNX3 expression were enhanced during hBMSC osteogenic differentiation. PART1 deletion decreased OCN, OSN, and COL1A1 levels and weakened ALP activity, but promoted the apoptosis of hBMSCs. Moreover, PART1 served as a ceRNA to influence the RUNX3 level via targeting miR-185-5p. In addition, RUNX3 was verified to activate the transcription of PART1 in hBMSCs. Finally, rescue assays indicated that suppression of miR-185-5p or addition of RUNX3 partially abolished the effects of PART1 knockdown on the levels of OCN, OSX, and COL1A1 levels, ALP activity, and apoptosis. Conclusion Our study elaborated that PART1/miR-185-5p/RUNX3 feedback contributed to osteogenic differentiation and inhibited the hBMSCs apoptosis, suggesting that PART1 might be a novel target for OP treatment.